2019
DOI: 10.3390/ijms20163984
|View full text |Cite
|
Sign up to set email alerts
|

How Plants Handle Trivalent (+3) Elements

Abstract: Plant development and fitness largely depend on the adequate availability of mineral elements in the soil. Most essential nutrients are available and can be membrane transported either as mono or divalent cations or as mono- or divalent anions. Trivalent cations are highly toxic to membranes, and plants have evolved different mechanisms to handle +3 elements in a safe way. The essential functional role of a few metal ions, with the possibility to gain a trivalent state, mainly resides in the ion’s redox activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 209 publications
(232 reference statements)
0
15
0
Order By: Relevance
“…One of the main strategies reported for Al exclusion is mediated by organic acid (OA) efflux from the root apex (Yang et al, 2013;Poschenrieder et al, 2019), a ubiquitous mechanism in all plant cells that reduces Al damage by forming stable compounds with Al 3+ ions in the rhizosphere (Bojórquez-Quintal et al, 2017). The first genes linked to Al tolerance were malate and citrate organic acid transporters in wheat (Triticum aestivum), sorghum (Sorghum bicolor), and barley (Hordeum vulgare) (Sasaki et al, 2004;Furukawa et al, 2007;Magalhaes et al, 2007).…”
Section: Genetic Mechanisms Underlying Heavy Metal Tolerancementioning
confidence: 99%
“…One of the main strategies reported for Al exclusion is mediated by organic acid (OA) efflux from the root apex (Yang et al, 2013;Poschenrieder et al, 2019), a ubiquitous mechanism in all plant cells that reduces Al damage by forming stable compounds with Al 3+ ions in the rhizosphere (Bojórquez-Quintal et al, 2017). The first genes linked to Al tolerance were malate and citrate organic acid transporters in wheat (Triticum aestivum), sorghum (Sorghum bicolor), and barley (Hordeum vulgare) (Sasaki et al, 2004;Furukawa et al, 2007;Magalhaes et al, 2007).…”
Section: Genetic Mechanisms Underlying Heavy Metal Tolerancementioning
confidence: 99%
“…In general terms, it is accepted that important toxic metal elements are in contact with the root tip and can be internalized via symplast or apoplast, depending on their chemical nature [ 11 ]. Most of the plant´s constitutive transporters are part of the active transport system that functions with divalent cations (Ca 2+ and Mg 2+ ); therefore, many of the metal(oid) elements that have this chemical valence will find them suitable for entrance into the root tip [ 18 ]. Trivalent ions, such as Al 3+ , are not so abundant in nature but can be liberated due to human activity; thus, only one transporter has been related to Al 3+ uptake in plants: NRAMP Aluminum Transporter 1 (NRAT1) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although, under B toxicity, normally BOR1 is quickly degraded to avoid excessive transport of B to the shoot (Poschenrieder et al 2019), in rice an enhancement of other aquaporins, such as OsPIP2,4 and OsPIP2,7 (Kumar et al 2014), to augment B movement to the leaves, was observed. Sutton et al (2007), in barley plants, demonstrated an enhanced expression of efflux transporters in cells of leaves and roots; the key to tolerance lies in an increase in B efflux from the sensitive symplast to the apoplast, with later efflux of this B from hydathodes to the leaf surface, mediated by BOR1 (Reid and Fitzpatrick 2009).…”
Section: The Influence Of Deficiencies Of Micronutrients On the Intermentioning
confidence: 99%